Effects Of Nanoparticles Concentration To Transport Properties Of Nanofluids Using Molecular Dynamics Simulation - Abdullah, Umar Mujahid (Universiti Sains Malaysia, 2019)
Nanofluid has a big potential to replace conventional fluid as heat transfer medium. Nanofluid consists of nanoparticles with size range 1-100nm and been dispersed in a base fluid. The existence of nanofluid is to improve the transport properties of base fluid. However, the main challenge to accomplish this is the lack of knowledge related to atomic physics. The common problem faced is the increases of viscosity in order to attain a higher thermal conductivity. To fill the research gap, the objectives of this thesis are to study the effect of nanoparticles towards viscosity and thermal conductivity at a desired temperature. Molecular dynamic simulation using Green Kubo method was implemented to conduct the simulation of dispersion of nanoparticles in nanofluid. Copper nanoparticles have been chosen to simulate with water. In the end of simulation, it is found out that density of water increased when the nanoparticles are dispersed into the water. The density of water increased with the addition number of copper atoms in the system. The viscosity and thermal conductivity also increased respected to the increase of nanoparticles concentration. There was a big increasing in viscosity value that might cause by composition of copper to copper atoms. There also showed an obvious increasing in thermal conductivity which is too significant.